The impact of cases and death reports of COVID-19 on prices and returns - Jeffrey Steanly Saputra; Jessica Jeniver Manuho; Riska Maunde; Renitha Aprilia Gracia Thomas (Yayasan Widyantara Nawasena Raharja, 2022)
Both the technology sector and the health sector are important issues for investors during the COVID-19 pandemic in 2021. This study aims to examine the impact of cases and death reports on the prices and stock returns especially for firms in the technology and health sectors. On this purpose, the sample is taken for the period January 4 2021 to December 30, 2021. The results of correlation and mean difference tests show that cases and death reports of COVID-19 are not the main cause in influencing stock prices and stock returns of both sectors. The findings suspect that management performance or prospects of the two sectors will trigger synergy in creating a unidirectional relationship between stock prices and stock returns.